Pembelajaran Pendidikan Agama Islam Berbasis Proyek - Budiono, Slamet; Sanusi, M.; Ghafur, Octa Abdul; Ardianto, Risko Aris (TSAQOFAH, 2024)
The project method is a way of teaching that provides students with the opportunity to use daily life units as learning material and aims to make students interested in learning. The project learning method is a teaching and learning activity whose process is based on inquiry. In this learning, the focus is on complex questions and problems. Then answer questions or solve problems through an investigative process carried out collaboratively over time. Most projects are carried out by investigating authentic issues and topics found outside of school. During the inquiry process, students learn the content, information and facts needed to draw conclusions from each question. During the process students also learn valuable skills and thinking habits. The project-based learning method is a learning method that uses problems as the first step in collecting and integrating new knowledge based on experience in real activities. Then the problem is solved in groups. In this learning, students are able to find their own solutions to the products/tasks given. Project-based learning methods can increase students' learning motivation in Islamic religious education, project-based learning methods can facilitate more active learning experiences.